Elucidating the functional evolution of heat sensors among Xenopus species adapted to different thermal niches by ancestral sequence reconstruction - Shigeru Saito; Claire T. Saito; Masafumi Nozawa; Makoto Tominaga (Molecular Ecology, 2019)
Ambient temperature fluctuations are detected via the thermosensory system which allows animals to seek preferable thermal conditions or escape from harmful temperatures. Evolutionary changes in thermal perception have thus potentially played crucial roles in niche selection. The genus Xenopus (clawed frog) is suitable for investigating the relationship between thermal perception and niche selection due to their diverse latitudinal and altitudinal distributions. Here we performed comparative analyses of the neuronal heat sensors TRPV1 and TRPA1 among closely related Xenopus species ( X. borealis , X. muelleri , X. laevis , and X. tropicalis ) to elucidate their functional evolution and to assess whether their functional differences correlate with thermal niche selection among the species. Comparison of TRPV1 among four extant Xenopus species and reconstruction of the ancestral TRPV1 revealed that TRPV1 responses to repeated heat stimulation were specifically altered in the lineage leading to X. tropicalis which inhabits warmer niches. Moreover, the thermal sensitivity of TRPA1 was lower in X. tropicalis than the other species, although the thermal sensitivity of TRPV1 and TRPA1 was not always lower in species that inhabit warmer niches than the species inhabit cooler niches. However, a clear correlation was found in species differences in TRPA1 activity. Heat‐evoked activity of TRPA1 in X. borealis and X. laevis , which are adapted to cooler niches, was significantly higher than in X. tropicalis and X. muelleri which are adapted to warmer niches. These findings suggest that the functional properties of heat sensors changed during Xenopus evolution, potentially altering the preferred temperature ranges among species.